Deployment of ICT for School Administration in Public Secondary Schools in North-Central Geo-Political Zone, Nigeria - Madu Christian Onyekachi; Yahaya Danjuma Mohammed (Researchparks Publishing, 2021)
Information communication technology(s) is vital to the realization of secondary school objectives. As important as these ICT resources to the development of education especially the secondary school education in the North-central Nigeria. It is unfortunate that many public secondary schools in the zone have not fully deployed the ICT for school administration. This paper discusses the challenges militating against deployment of ICT for school administration in the zone. The paper depends on empirical documents to provide support for the various points raised in the paper. The paper established that information communication technology (s) is aiding effective school administration at the secondary school. Inadequate funding, inadequate ICT facilities, unstable power supply, unstable internet services, high cost of ICT facilities, poor computer literacy, poor implementation of ICT policies and shortage of ICT manpower were identified as challenges militating against deployment of ICT for school administration in north-central political zone of Nigeria. Based on the finding, the paper recommended that the government should increase the funding of public secondary school education and more priority should be given to ICT education in all the Secondary School in the North-Central Geo-Political zone. The government should provide more ICT facilities to all the public secondary schools in the north-central geo-political zone to enable the schools to deploy ICT facilities for school administration, teaching and learning in the classroom etc.